Answer:
The correct answer is the second option: ![s=\sqrt{\frac{R-3}{t}}](https://tex.z-dn.net/?f=s%3D%5Csqrt%7B%5Cfrac%7BR-3%7D%7Bt%7D%7D)
Step-by-step explanation:
The idea is to get the variable
for alone on one side. To do that follows the following steps:
1. Pass the number
to subtract to the left.
![R=t\cdot s^2+3](https://tex.z-dn.net/?f=R%3Dt%5Ccdot%20s%5E2%2B3)
![R-3=t\cdot s^2](https://tex.z-dn.net/?f=R-3%3Dt%5Ccdot%20s%5E2)
2. Pass the letter
to divide to the left side.
![\frac{R-3}{t}=s^2](https://tex.z-dn.net/?f=%5Cfrac%7BR-3%7D%7Bt%7D%3Ds%5E2)
3. Take the squared root on both sides.
![\sqrt{\frac{R-3}{t}}=\sqrt{s^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7BR-3%7D%7Bt%7D%7D%3D%5Csqrt%7Bs%5E2%7D)
4. The right part can be simplified to
because the power and the root are canceled.
![\sqrt{\frac{R-3}{t}}=s](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7BR-3%7D%7Bt%7D%7D%3Ds)
5. The solution of the equations is:
![s=\sqrt{\frac{R-3}{t}}](https://tex.z-dn.net/?f=s%3D%5Csqrt%7B%5Cfrac%7BR-3%7D%7Bt%7D%7D)
Thus, the correct answer is the second option: ![s=\sqrt{\frac{R-3}{t}}](https://tex.z-dn.net/?f=s%3D%5Csqrt%7B%5Cfrac%7BR-3%7D%7Bt%7D%7D)